PELAYANAN KARTU KELUARGA DI KECAMATAN MUARA HARUS KABUPATEN TABALONG - Muhammad Noor Ifansyah1 (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
Service is the main task of the essentials of the figure of the apparatur, as civil servants and the servant society. Employee of Government has not fully provide services to the community satisfy changes that can be felt today is the changing mindset of society toward an increasingly critical. The aim of this study is the author wanted to know how the service that is provided by the District Muara Harus to society, particularly in the manufacture of Family Card.The purpose of this study was to know how public services in Muara Harus. The method used in this research is descriptive qualitative data analysis by using techniques that later this informant to guide researchers in obtaining data relating has investigated by researchers.From the results of the study on the basis of the questions obtained an explanation that the Office of Muara Harus District Must still fundamental changes in providing services to the applicants card-making family. This can be seen by: 1) Procedure service, there are still complaints about service personnel accuracy Card making family because there is slowness and lack of earnest in service delivery, so it needs to be improved so that as a public servant as expected by the public; 2) The time of service, although the implementation of the Family Card making using the computer, but as the engine power is sometimes impaired.